52.9k views
2 votes
Find the inverse of g(x) = -2x/3 -5

User VanAlbert
by
5.1k points

1 Answer

7 votes

The condition for an inverse function is:


g(x)=y\longrightarrow g^(-1)(y)=x

Then, we can calculate:


\begin{gathered} g(g^(-1)(x))=x \\ (-2g^(-1))/(3)-5=x \\ -(2)/(3)\cdot g^(-1)=x+5 \\ g^(-1)=-(3)/(2)(x+5) \\ g^(-1)=-(3)/(2)x-(15)/(2) \end{gathered}

The inverse of g(x) is:


g^(-1)(y)=-(3)/(2)y-(15)/(2)

User Rkabhishek
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.